Re-Thinking Access to Criminal Justice in Canada: A Critical Review of Needs and Responses - Hughes, Patricia (2002)
This paper provides a critical assessment of some current issues about access to justice in Canada, with a special focus on criminal justice. The paper identifies recent trends in the literature about criminal justice in Canada and in related common law jurisdictions, including the United States, the United Kingdom, Australia and New Zealand; and the development of restorative justice processes to augment or replace traditional approaches to criminal justice. Overall, the paper is intended to provide a review of selected literature with critical commentary about current trends in criminal justice, and to offer suggestions about empirical and other research initiatives designed to assess future needs. In Chapter I, the paper provides a conceptual framework for re-thinking access to criminal justice in Canada, linking scholarly work on access to justice from a number of different jurisdictions over the past few decades to current issues and developments in Canada. This chapter provides a contextual framework for assessing these issues with respect to: the relationship between civil and criminal justice issues; the goals of the criminal justice process, of punishment and of sentencing, and the goals of restorative justice. The conceptual framework also includes an assessment of the public and private dimensions of criminal justice through an examination of the idea of community in the context of individual relationships of power; and an exploration of the potential for achieving social change within restorative justice programmes. As well, the paper reviews critical literature about the impact of criminal justice processes on norms of equality and social justice. Chapter H provides a critical assessment of literature about the needs of participants in relation to criminal justice. Although the literature on legal needs is extensive, it is mainly focussed on needs in the context of civil law actions rather than in criminal justice. The paper examines the needs of three groups of participants in criminal justice processes: aboriginal offenders and their communities; criminal justice offenders, including women and visible minorities; and victims and communities. The paper explores issues about the relationship between needs and rights in criminal justice processes, and some fundamental issues - including relationships of power - among those involved in criminal justice. In doing so, this chapter identifies concerns about traditional and restorative justice practices in balancing rights and needs for participants in criminal justice. Chapter III of the paper provides an assessment of restorative justice principles, including a detailed examination of the theoretical goals and methods which have been identified in different contexts and jurisdictions. As the chapter explains, restorative justice has been described as a revolution in criminal justice / and a paradigm shift. 2 Chapter 3 examines the relationship between restorative justice practices and traditional criminal justice in Canada, and assesses how restorative justice responds to needs of participants in the criminal justice system. In doing so, the paper reviews a number of different restorative justice initiatives in Canada and in other jurisdictions, and particularly the three main kinds of programmes; victim-offender mediation, family group conferencing, and circle sentencing and other initiatives in aboriginal communities. In Chapter IV, the paper offers some reflections on restorative justice and its challenges. Recognizing the limits of current criminal justice processes, and the needs of criminal justice participants, the paper provides a critical assessment of restorative justice alternatives. It raises concerns about the identity of community, the potential for conflict between victims and communities, whether restorative justice programs are more a form of downloading of government services than an attempt to develop radical new approaches to criminal justice, the relationship between the mainstream criminal system and restorative justice practices and whether restorative justice practices are sufficiently cognizant of structural imbalances of power and the impact of gender, race and class on victims and offenders. As well, the paper identifies directions for further research to enable us to better assess the potential use of restorative justice principles in practice in Canada, with particular emphasis on general evaluation of restorative justice programs and the need to assess programs to determine whether they satisfy equality principles